2017
DOI: 10.1038/s41598-017-13507-9
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Antioxidant Peptides from Pepsin Hydrolysate of Whey Protein Isolate by ATPS of EOPO Co-polymer (UCON)/Phosphate

Abstract: An aqueous two-phase system (ATPS) consisting of poly(ethylene glycol-ran-propylene glycol) monobutyl ether (UCON)/phosphate was developed for the separation of the antioxidant peptides from pepsin hydrolysate of Whey Protein Isolate (WPI). The efficiency of the separation was evaluated based on the DPPH radical scavenging activity, ABTS radical scavenging activity and ferric reducing antioxidant power (FRAP) of the separated peptides. The effects of some parameters on the partition of antioxidant peptides wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…Xie et al discovered that the highly hydrophobic peptides from casein had excellent antioxidant activity [22]. Jiang et al reported that the highly hydrophobic and less polar peptides had excellent antioxidant activity [9]. Therefore this indicates that peptides from the bottom phase of ATPE had little antioxidant activity and peptides from the top phase of ATPE had excellent antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Xie et al discovered that the highly hydrophobic peptides from casein had excellent antioxidant activity [22]. Jiang et al reported that the highly hydrophobic and less polar peptides had excellent antioxidant activity [9]. Therefore this indicates that peptides from the bottom phase of ATPE had little antioxidant activity and peptides from the top phase of ATPE had excellent antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 showed that the special VGINYWLAHKALCSEK, KILLDKVGINYWLAHK, ILLDKVGINYWLAHK, IIAEKTKIPAVFK, KIIAEKTKIPAVFK, and VYVEELKPTPEGDLEILLQK sequences found in the peptides of the top phase of ATPF contained the AHK, IPAVF [27], YVEEL [9] peptides, all of which have antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antioxidant activity of peptides can be influenced by amnio acid content and position within the chain. The amino acids histidine, tyrosine, lysine, phenylalanine, valine, and cysteine were significantly higher in whey protein-derived peptides than in WPI hydrolysate, suggesting that these amino acids are essential for antioxidant activity [ 58 ]. The hexapeptide YFYPEL is generated by pepsin hydrolysis of bovine casein and scavenges superoxide radicals [ 51 ].…”
Section: Physiological Properties Of Food-derived Bioactive Peptidesmentioning
confidence: 99%